Metamodeling of structural failure: case study of API S-135 steel tube cut in BOP. - Lukin, Nikolas (2020)
In offshore oil exploration, it is necessary the use of a Dynamic Positioning System (DPS) to maintain the platform at a fixed point regardless of the influence of the environment. In an event of failure, however, a drill string inside BOP (BlowOut Preventer) must be cut using its indenters and safely disconnected from the well. Therefore, it is needed an accurate and realistic virtual model of this failure process. Numerical model analysis, in addition to avoid expensive and complex experimental tests, allows, through post-processing tools, a detailed understanding of all phases of the failure process. On a first stage, API S-135 steel, a material commonly used to manufacture drill strings, is characterized using Johnson-Cook model (J-C) for plasticity and failure. The material parameters are obtained from experimental tensile tests on dog bone and 3-point bending beams specimens with different notch radii, covering a wide range of stress triaxialities. Experimental tests and numerical simulations were compared by means of stress-strain curves, Digital Image Correlation (DIC) and Scanning Electron Microscopy (SEM) to validate the model. The material model is applied to simulate the pipe cutting process and to predict the required force for the BOP to cut drill pipes with different geometries, which in comparison to experimental tests permitted to determine BOP internal frictions. Additionally, the numerical simulation also allowed a better understanding of the cutting process here presented as well, coherent to SEM imaging of a similar cut tube in BOP. The required force to cut the string is traditionally determined by analytical models and commissioning tests, which can be far from the real situations. Depending on boundary conditions of this tubular, the BOP may fail to cut it, which can lead to catastrophic events. In this way, a metamodel is defined to predict required forces for BOP to cut API S-135 6.63\'\' 40.87ppf drill pipes, with different boundary conditions. Different simulations in combined conditions, including initial traction and torque, pipe decentralization and indenter offsetting, were performed in order to find the required force in indentator to cut the pipe. Such data were used to develop a metamodel using feed a machine learning algorithm which leads to conclude that current BOP cutting models may underestimate the required force to cut pipe in realistic conditions.